Modeling development process of skill-based system for human-like manipulation robot. (18th May 2016) - Hanai, R.; Suzuki, H.; Nakabo, Y.; Harada, K.
Abstract : The importance of system integration is widely recognized in robotics. This motivates the application of Model-Based Systems Engineering (MBSE) approaches to improve the development process of robot systems. This paper models a development process to achieve given task goals using a human-like upper body robot based on MBSE approach. For this purpose, we focus on the domain knowledge of tasks and skills in robotics. Since MBSE is a general methodology, there is a lot of flexibility on the way of proceeding with the analysis and design, and how to utilize models there. Using the concept of tasks and skills is helpful for better uderstanding of the development process. Our process is based on three main concepts: (1) stakeholders of User and Developer, (2) coordination between User and Developer using skills as communication interface, (3) extension development. Making the process explicit helps many stakeholders such as robot makers, system integrators, and engineers in various application domains to join the system development. It is also effective for accumulating experiences and work products of the development. In addition, we can expect that better understanding of the engineering process results in the improvement of the process performed by automation tools and humans cooperatively. Graphical Abstract: